Correlation and path analysis of grain yield and its components for lentil under Shahrekord climate - Narges Bitaraf; Mahmood Khoddambashi; Sadolah Hooshmand (پژوهش‌های حبوبات ایران)
The purpose of this study was to describe the association between grain yield and its components.The experiment was conducted in a randomized complete block design with three replicatsions.Results of analysis showed that similar trends were observed for genotypic and phenotypiccorrelations and in most cases, the value for genetic correlation was greater than phenotypic value.100-seed weight revealed the greatest positive phenotypic correlation and plant height as well as 100-seed weight showed the greatest genotypic correlation with seed yield per plant. Path analysis usinggenotypic correlation coefficients pointed out that 100-seed weight, number of pods per plant, numberof nodes per main stem and number of clusters per plant had the greatest positive direct effects ongrain yield per plant, respectively. These traits included important factors determining seed yield inconcerned genetic materials.Key words: Correlations, Grain yield, Lentil, Path analysis, Yield component